Environmental Analytical Chemistry - Qu, Ke; Dan, Dezhong (Amsterdam : Elsevier, 2024)
Environmental Analytical Chemistry investigates how to use modern scientific theory and advanced experimental techniques to identify and determine the types, components, amounts, and chemical forms of substances in the environment, including both naturally occurring chemicals and anthropogenic contaminants. The book covers the newest developments of environmental analytical chemistry, including discussions of pretreatment techniques of environmental samples, chemical species and speciation analysis, atmospheric pollutants analysis, water pollutants analysis, soil pollutants analysis, sensing techniques for environmental pollutants and on-site rapid emergency analytical technology for environmental emergencies.
Includes index
Keywords: Soil Pollution; Chemical analysis; Environmental emergency; Water pollution